Online validation of software for cylindrical involute gears. (December 2021) - Lin, Shan; Stein, Martin; Keller, Frank; Härtig, Frank
Abstract: The validation of evaluation algorithms used in gear metrology enables manufacturers of measurement instruments to improve the reliability of measurement results. The incorrect usage of definitions and evaluation strategies in the current standards may lead to a systematic evaluation error in the gear software. In cooperation with industrial partners, an online validation system of gear software is under development. In the paper, evaluation strategies of tooth flank deviations are mathematically described according to a 3D involute gear model. These evaluation strategies as a part of reference software will be implemented in the TraCIM system at Physikalisch-Technische Bundesanstalt. The online validation of gear software, as well as test data sets, are also presented.